Pengaruh Blended Learning Terhadap Motivasi Dan Hasil Belajar Siswa Di Min 1 Tulungagung - Dhona Ayu Qomara; Agus Purwowidodo (The Elementary Journal, 2023)
This research aims: 1) To analyze the effect of implementing Blended Learning on the learning motivation of second-grade students at MIN 1 Tulungagung, 2) To analyze the effect of implementing Blended Learning on the learning outcomes of second-grade students at MIN 1 Tulungagung, 3) To analyze the effect of implementing Blended Learning on the motivation and learning outcomes of students at MIN 1 Tulungagung. The type of research used is a quasi-experiment with a population of all second-grade students at MIN 1 Tulungagung, totaling 64 students. Data collection techniques used questionnaires and post-tests, which were analyzed using parametric statistics with an independent T-Test. The research results show: 1) There is a difference in learning motivation between students taught with Blended Learning (experimental class) compared to students taught with conventional learning (control class) with a significance value of 0.002 and an average motivation of 89, 2) There is a difference in student learning outcomes with a significance value of 0.016 and an average learning outcome of 84, 3) There is an increase in student learning motivation due to the implementation of Blended Learning with a significance value of 0.002 and an increase in score by 11 points, as well as an increase in student learning outcomes with a significance value of 0.016 and an increase in score by 12 points.